Physicochemical Characteristics of Watermelon Rind Puree Ice Cream with Cornstarch Addition - Ali Jebreen; Maretha Indra Puspa; Safinta Nurindra Rahmadhia; Swapnil Prashant Gautam (Journal of Agri-Food Science and Technology, 2026)
Ice cream is a frozen dairy product made from milk and other ingredients such as sugar, emulsifier, and fruit for flavoring and enhance the nutrition content. Watermelon rind, which is rich in pectin that can form gel structures, is used for nutritional ingredient of ice cream. Pectin gel plays an important role in maintaining ice cream stability and reducing melting rate. In addition, cornstarch was added to the ice cream formulation for thickening and stabilization agent. This study contributed to evaluate the effect of watermelon rind puree and cornstarch addition on the physicochemical properties of ice cream. The ice cream production using comparison of watermelon rind puree and corn starch in three variations, namely 205:5 g (F1); 200:10 g (F2); and 195:15 g (F3). The observed parameters included overrun, viscosity, melting rate, fat content, vitamin C content, and antioxidant activity. The results showed that the addition of cornstarch had a significant effect on overrun, viscosity, melting rate, vitamin C content, and antioxidant activity, but had no significant effect on fat content. The melting rate and overrun value increased, while the highest viscosity was observed in F3 (1863.00 mPa.s). Antioxidant activity also increased significantly from F1 (42,300.52%) to F3 (54,882.33%). The highest vitamin C content was found in F3 (25.63 mg/100g). These findings indicate that the addition of cornstarch and watermelon rind puree improves the physical quality of ice cream and helps retain its bioactive compounds, with F3 identified as the best formulation.